Irenaeus"s knowledge of the Gospel of Judas: Real or false? An analysis of the evidence in context - Oort, Johannes van (HTS teologiese studies, 2013)
This study discusses Irenaeus of Lyon’s testimony of the famous Gospel of Judas, offering both a historical and, in particular, linguistic analysis and retranslation of Against Heresies 1.31.1. On the basis of a detailed philological commentary and textual analysis it is – contrary to most current opinions – concluded that Irenaeus, in all feasibility, had first-hand knowledge of the Gospel and its contents. In other words, Irenaeus appears to have read the text as we now have it (‘a composed work’) and he summarises it in his treatise. According to Irenaeus’s testimony, the Gospel was produced by a group of 2nd century Gnostics who positively venerated Judas as a fellow Gnostic in the same way that they positively venerated Cain. It was because of his particular knowledge of the redeeming act of Sophia as well as the negative characteristics of the creator God in contrast to the superior God that Judas accomplished the ‘mystery of his (= Jesus’) betrayal’, so that ‘through him (= Judas) all things, both earthly and heavenly, have been dissolved.’